Editorial - Kumar, Aruna T (Indian Farming, 2019)
THE delayed monsoon has finally arrived and for farmers there is so much to plan and so much to do; from sowing of kharif crops to management of weeds and insect-pests. Farmers look into conservation of resources, and sustainability and diversification of system. Prior planning for all agricultural practices is easier said than done. Farming in a normal season and after a natural disaster (like flood and drought) requires altogether different finances and expertise, along with heart and courage of the ever optimistic Indian farmer who faces these calamities in one or the other part of India, year after year.